VERNACULAR ARCHITECTURE OF BUNISAKTI VILLAGE: SETTLEMENT PATTERNS, TRADITIONAL HOUSES, AND LOCAL WISDOM IN THE NUSANTARA’S PERSPECTIVE - Priarana, Suwardi Alamsyah; Rusnandar, Nandang (Jurnal Tradisi Lisan Nusantara, 2025)
Abstract; Kampung Bunisakti is one of the traditional villages in the archipelago that stores the richness of vernacular architecture through its traditional settlement patterns and houses. The vernacular architecture in this village is not just a physical form of a building, but a manifestation of local wisdom born from human interaction with nature, culture, and cosmology. This article aims to analyze the patterns of villages and houses of Kampung Bunisakti with a vernacular architectural approach, as well as relate them to the symbolic values contained in them. The research method used is qualitative-descriptive through field data analysis and literature, combined with vernacular architectural theories from Paul Oliver and Amos Rapoport. The results of the study show that the spatial layout of the village and the shape of traditional houses in Bunisakti reflect the ecological, spiritual, and social relations of the community. The village pattern is built by taking into account cosmological orientation, connectivity with the natural landscape, and inter-house relationships that affirm the social bonds of the community. Meanwhile, traditional houses combine practical functions with cultural symbolism, such as the use of local materials, the division of space by gender and age, and meaningful ornaments. This analysis confirms that the vernacular architecture of Bunisakti Village is a representation of cultural identity as well as ecological knowledge that is relevant to contemporary architectural challenges. Thus, this study contributes to a broader understanding of the vernacular architecture of the archipelago, as well as opens up opportunities for the development of sustainable architecture based on local wisdom.